2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6883986
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of communication networks for smart substations using a virtualized execution platform

Abstract: The current development of the power grid towards a Smart Grid advances the complexity of the system, involving active control, new software components and large amounts of data. This, in turn, requires new approaches for the ICT infrastructure to guarantee real-time capability and reliability. In this work, we present our design of a novel infrastructure for smart substations in the transmission grid, applying the concept of virtualization to substation devices. Since virtualization has already been successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For instnace, the concept of virtualization in substation communication is presented in [228], [229]. By using the virtualization concept in substation, dynamic configuration and management case be easily performed.…”
Section: ) Simulations Related Issues In Sdn-based Sgcmentioning
confidence: 99%
See 1 more Smart Citation
“…For instnace, the concept of virtualization in substation communication is presented in [228], [229]. By using the virtualization concept in substation, dynamic configuration and management case be easily performed.…”
Section: ) Simulations Related Issues In Sdn-based Sgcmentioning
confidence: 99%
“…By using the virtualization concept in substation, dynamic configuration and management case be easily performed. Dorsch et al [228] basically considers two type of traffic i.e., substation traffic based on IEC 61850 standard and traffic related to virtualization. Extensive simulations for double star infrastructure, single Infrastructure, and dedicated infrastructure substation scenarios, were conducted in OPNET Modeler and it is concluded that SDN should be incorporated to use virtualization at network level.…”
Section: ) Simulations Related Issues In Sdn-based Sgcmentioning
confidence: 99%
“…However, as proposed in [Bob+14], communication networks involved in the operation of the electric grid, must meet requirements that are not the same as the ones of a corporate network. Hence, several studies have evaluated the advantages and disadvantages of incorporating SDN and virtualization technologies in the current operation of a power substation communication network [PD14;Dor+14b;Don+15;KFK15;Dor+14a;Luw14].…”
Section: Introductionmentioning
confidence: 99%